Control of Skin Potential by Triboelectrification with Ferroelectric Polymers. (20th August 2015) - Lee, Ju‐Hyuck; Hinchet, Ronan; Kim, Tae Yun; Ryu, Hanjun; Seung, Wanchul; Yoon, Hong‐Joon; Kim, Sang‐Woo
<x xml:space="preserve">Abstract</x> Negatively polarized ferroelectric polymer β‐P(VDF‐TrFE) shows higher positive triboelectric properties than skin, which could lead to new medical applications. Kelvin force microscope measurements and triboelectric nanogenerator characterizations are performed to demonstrate this new property. In addition, how many negative charges are exchanged by contact electrification between the negatively polarized β‐P(VDF‐TrFE) and the skin is estimated.